2017
DOI: 10.1002/2016sw001559
|View full text |Cite
|
Sign up to set email alerts
|

Geoeffectiveness of stream interaction regions during 2007–2008

Abstract: The stream interaction regions (SIRs) are generated in the interplanetary medium when a fast solar wind stream overtakes a slower one. If these large‐scale phenomena interact with the Earth's magnetosphere, they can give rise to geomagnetic storms (GSs). Their geoeffectivity is measured using magnetic indices at different latitudes. In this study we analyzed the geoeffectiveness of 20 GSs that were generated by SIRs during the period of 2007 to 2008 and observed by the ACE, Wind, and STEREO‐A/B spacecraft. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
(102 reference statements)
1
4
0
Order By: Relevance
“…In cycle 24, 17 SIRs (28%) caused a GS. As expected from previous studies, the GSs associated with the SIR events were minor or moderate (Chi et al., 2018; Sanchez‐Garcia et al., 2017). Figure 7b shows the histogram of GSs generated by the SIRs according to the Dst index.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In cycle 24, 17 SIRs (28%) caused a GS. As expected from previous studies, the GSs associated with the SIR events were minor or moderate (Chi et al., 2018; Sanchez‐Garcia et al., 2017). Figure 7b shows the histogram of GSs generated by the SIRs according to the Dst index.…”
Section: Resultssupporting
confidence: 86%
“…B z is an essential signature in forecasting a geomagnetic response (Richardson, 2018). The level of geomagnetic activity is also correlated with the high‐speed stream and tends to be stronger during the disturbed fast SW (Richardson, 2018; Sanchez‐Garcia et al., 2017; Verbanac et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…SIRs are thought to be the major drivers of moderate geomagnetic storms (e.g., Echer et al, ; Shen et al, ; Zhang et al, , and references therein). From another point of view, the geoeffectiveness of SIRs has also been widely studied by different authors (e.g., Alves et al, ; Kilpua et al, ; Lockwood et al, ; Sanchez‐Garcia et al, ; Zhang et al, ). Using solar wind observations during the period from 1964 to 2003, Alves et al () found that 33% of SIRs were followed by moderate/intense magnetic activity ( D s t ≤−50 nT).…”
Section: Introductionmentioning
confidence: 99%
“…They further suggested that SIRs had a greater geomagnetic effect than expected. Sanchez‐Garcia et al () studied the geoeffectiveness of SIRs during 2007 and 2008. They found that the percentage of SIRs causing geomagnetic storms was 50%, 55%, and 90% using the criteria of the aa, Kp, and equivalent symmetric disturbance component in H (SYM‐H) indices, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…CMEs drastically disturb the cosmic ray (CR) intensity (CRI; e.g., Cane, ; Oh et al, ; Venkatesan & Badruddin, ; G. Zhang & Burlaga, ). They cause large disturbances in geomagnetic activity (e.g., Kamide et al, ; Yermolaev et al, ; J. Zhang et al, ) and are responsible for other space weather effects (e.g., Kudela et al, ; Sanchez‐Garcia et al, , and references therein). Periods, when several solar flares occur and CMEs (especially halo CMEs) are ejected from the Sun subsequently and travel in the interplanetary space, are of special interest for the study of the evolution and effects of disturbances in the heliosphere and magnetosphere.…”
Section: Introductionmentioning
confidence: 99%